Catalytic conversion of bioethanol to value-added chemicals and fuels: A review - Huan Xiang; Ruojia Xin; Natthawan Prasongthum; Paweesuda Natewong; Tawan Sooknoi; Jiawei Wang; Prasert Reubroycharoen; Xiaolei Fan (My University, 2022)
Bioethanol produced via valorisation of renewable biomass is of great interest to many industries. The increased availability and decreased cost of bioethanol make it a promising platform molecule to produce a wide range of value-added chemicals and fuels via the catalytic conversions. This paper provides a comprehensive review of catalytic conversions of bioethanol to a variety of chemicals/fuels such as hydrogen, C2–C4 olefins, gasoline and small oxygenates. Specifically, the focus was placed on the relationship between the catalyst property (such as pore structure, acidity, active metal sites, and catalyst supports) and the catalytic performance (including catalyst activity and stability), as well as the reaction mechanisms involved. Future research avenues on the catalyst design for improving catalytic valorisation of bioethanol are also discussed.
Keywords: Oxygenate; Valorisation; Renewable Fuels; Commodity chemicals; Catalysis for Biomass Conversion